Performance and running experience of the Belle II silicon vertex detector. Issue 1 (1st November 2022) - Nakamura, K. R.; Adamczyk, K.; Aggarwal, L.; Aihara, H.; Aziz, T.; Bacher, S.; Bahinipati, S.; Batignani, G.; Baudot, J.; Behera, P. K.; Bettarini, S.; Bilka, T.; et al.
Abstract : The Belle II silicon vertex detector is one of the vertex detectors in the Belle II experiment. The detector reads out the signals from the double-sided silicon strip sensors with the APV25 front-end readout ASIC, adopting the chip-on-sensor concept to minimize the strip noise. The detector has been operated in the experiment since the spring of 2019. Analyzing the acquired data during the beam collisions, the excellent performance of the detector is confirmed. Also, the radiation dose and 1-MeV equivalent neutron fluence of the detector are estimated using the measured dose rates of the diamond sensors installed on the beam pipe and are compared with the measured radiation effects in the strip noise, leakage current, and depletion voltage. This paper briefly introduces the main features of the silicon vertex detector, and then reports on the measured performance and radiation effects of the first two years of running experience of the detector.